Conocimiento de los derechos del consumidor en la ley 29571 en los ciudadanos de Iquitos metropolitano junio 2024 - Yahuana Alba, Roder (2025)
The research was developed with the objective of determining the level of knowledge that the citizens of Metropolitan Iquitos have about their rights as consumers as established in Law 29571, Consumer Protection and Defense Code, for which the quantitative approach was applied non-experimental cross-sectional design, descriptive level and basic type. The findings of the study determine that the level of knowledge of consumer rights in metropolitan Iquitos is moderate, with a relative value of 39.6%. The disaggregated result between its districts such as Belén, the level of knowledge of consumer rights is high at 46.3%; Iquitos, the level of knowledge of consumer rights is predominantly low at 56.3%; Punchana, the level of knowledge of consumer rights is predominantly moderate with 42%; and, San Juan Bautista, the level of knowledge of consumer rights is predominantly high with 39.52%. It is concluded that the level of knowledge that the citizens of Metropolitan Iquitos have is moderate.